Spatial Model of Micro Climate Assessment and Recommendation of Mitigation In Semarang City With Remote Sensing Technology. (August 2019) - Sasmito, B; Suprayogi, A; Awaluddin, M; Darlina, S P; Andani, N D; Kalinda, I O P
Abstract: The city of Semarang is one of the 10 major cities in Indonesia that are developing towards the metropolis. Urban infrastructure develops, resulting in the use of vegetation land to be converted into build up land. The increasingly hot climate of the city will disrupt the comfort of residents. Urban design and planning should consider land use change. Good planning will have a very good effect on the city's climate system. This study aims to examine the phenomenon of micro-climate change in the city with the algorithm of the Temperature Heat Index (Leisure Index). The assessment starts from the Land Surface Temperature algorithm, from here model of Urban Heat Island (UHI) can be done. The distribution of UHI phenomena is derived from Land Surface Temperature. The UHI mitigation recommendation for Semarang City is based on land cover. The method used is the Remote Sensing approach through some spatial data extraction from satellite imagery. Data processing is done by using multi-temporal data of Landsat 8 satellite imagery. The result is presented in thematic map of LST, UHI, and Mitigation model map. Mitigation that can be done is the physical modification of the building, like the use of material with high albedo, the application of green wall, green roof, greening parking lots, and the addition of vegetation around the building and along the road. Besides, it is also necessary to monitor the change of land function and its suitability with the Urban Land use Plan of Semarang City.